Going Local on a Global Platform: A Critical Analysis of the Transformative Potential of Cryptomarkets for Organized Illicit Drug Crime. (September 2018) - Demant, Jakob; Munksgaard, Rasmus; Décary-Hétu, David; Aldridge, Judith
Objective: There is broad agreement in the literature on the transformative potential of drug cryptomarkets that allow sourcing on a global market and consequently the circumvention of existing supply chains between producer and end user. We examine whether the transformative potential of drug cryptomarkets has been realized in two ways: Are cryptomarket drug sellers found in production and transit countries? and Do we see the increased use of shipping across international borders over time? Method: Using data collected by the DATACRYPTO software tool between 2013 and 2016, we characterize cryptomarket buyer behavior through the product reviews (i.e., sales transactions) posted on 15 cryptomarkets. Findings: Cryptomarket drug sellers are predominantly based in countries of Europe, North America, and Oceania. For both cannabis resin and cocaine sold on cryptomarkets, we find that known production and transit countries are not the primary sources of supplied drugs but rather key countries of consumption. In the case of 3, 4-methylenedioxymethamphetamine, we observe that the Netherlands, a known production country, is the largest supplier. We further observe tendencies over time toward increased localization of cryptomarkets with regard to product destinations. Discussion: Though cryptomarkets offer a potentially global platform for drug distribution, they do not tend to be used as such. We explain our results with reference to buyers' preferences regarding safety, risk, and convenience, alongside structural limitations for cryptomarket use such as bitcoin availability.